Sistem Aplikasi Penyelesaian Masalah Program Linier Standar Maksimal Berbasis Web dengan Keluaran Sesuai Produk Kemasan terkecil - Sriwasito, Putut; Surarso, Bayu; Sarwoko, Eko Adi (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
Individual or cooperation  as the producer who produces more than one product always has a problem to determine the amount of each product, as well as the smallest packaging used to generate the maximum revenue but still meet the inventory of existing facilities. If the inventory of facilities and functions form a linear function of income then the problem is called the program a maximu m linear case, where all supplies are  limited means of the standard linear program is called maximal. Although the system has available a linear program to solve the problem,  the system is only owned by a limited circle, this system also   does not provide the smallest packaging option.  In general linear programming problem is solved by the simplex method with any number of real output in decimal or fractional format  mix.  Settlement  is  not  operational  because  the  manufacturers  do  not  always  able  to  make  the  smallest  product  packaging   in accordance with the unit on completion, to become operational, the results of this settlement may be rounded according to the smallest package selected. The problem of limited manufactures which have a system of linear program application can be overcome by providing a system similar to a web-based applications. This study compiled a web-based application system to solve a standard linear program that generates the maximum revenue that maximum use PHP software, data entered through the form and then taken by the POST method, then set up a matrix, carried out by iterating between the rows in the matrix operations that met the criteria optimal. By ch oosing the smallest packaging  which is used  0.25 units or 0.50  units, the system  check the number of products that  have  the smallest rounding according to the package selected, then the system prepare and present the inventory and revenue report.Keywords: Simplex metho; The smallest packaging; Web-based